High EVI1 and PARP1 expression as favourable prognostic markers in high-grade serous ovarian carcinoma - Jank, Paul; Leichsenring, Jonas; Kolb, Svenja; Hoffmann, Inga; Bischoff, Philip; Kunze, Catarina Alisa; Dragomir, Mihnea P.; Gleitsmann, Moritz; Jesinghaus, Moritz; Schmitt, Wolfgang D.; Kulbe, Hagen; Sers, Christine; et al. (Journal of ovarian research, 2023)
Background: Mechanisms of development and progression of high-grade serous ovarian cancer (HGSOC) are poorly understood. EVI1 and PARP1, part of TGF-ß pathway, are upregulated in cancers with DNA repair deficiencies with DNA repair deficiencies and may influce disease progression and survival. Therefore we questioned the prognostic significance of protein expression of EVI1 alone and in combination with PARP1 and analyzed them in a cohort of patients with HGSOC. Methods: For 562 HGSOC patients, we evaluated EVI1 and PARP1 expression by immunohistochemical staining on tissue microarrays with QuPath digital semi-automatic positive cell detection. Results: High EVI1 expressing (> 30% positive tumor cells) HGSOC were associated with improved progression-free survival (PFS) (HR = 0.66, 95% CI: 0.504–0.852, p = 0.002) and overall survival (OS) (HR = 0.45, 95% CI: 0.352–0.563, p < 0.001), including multivariate analysis. Most interestingly, mutual high expression of both proteins identifies a group with particularly good prognosis. Our findings were proven technically and clinically using bioinformatical data sets for single-cell sequencing, copy number variation and gene as well as protein expression. Conclusions: EVI1 and PARP1 are robust prognostic biomarkers for favorable prognosis in HGSOC and imply further research with respect to their reciprocity.
Veröffentlicht: 31. Juli 2023
Gesehen am 09.10.2023